2019
DOI: 10.24106/kefdergi.2719
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de İlköğretimde Görsel Sanatlar ile ilgili Yapılan Lisansüstü Tezlerin Eğilimleri

Abstract: Bu araştırmanın amacı, Türkiye'de ilköğretim düzeyinde görsel sanatlar ile ilgili yapılan lisansüstü tezlerin içerik analizini yaparak eğilimlerini belirmektir. Bu amaçla, YÖK ulusal tez veri merkezinden ilköğretim ve görsel sanatlar ile ilgili anahtar kelimeler gelişmiş tarama yapılarak 84 tane tez nitel araştırma kapsamında içerik analizi ile analiz edilmiştir. Bu araştırma, erişme izin durumundan "izinli" tezler seçilerek, geçmişten 2016 yılın sonuna kadar yapılan tezler ile sınırlandırılmıştır. Araştırmada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Results also revealed that articles related to art education, communication and society mostly used qualitative research method. Consistent with this result, Namdar and Onder (2018) examined trends in postgraduate thesis on visual arts in Turkish primary education and found that qualitative research method was mostly carried out in the postgraduate thesis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Results also revealed that articles related to art education, communication and society mostly used qualitative research method. Consistent with this result, Namdar and Onder (2018) examined trends in postgraduate thesis on visual arts in Turkish primary education and found that qualitative research method was mostly carried out in the postgraduate thesis.…”
Section: Discussionmentioning
confidence: 62%
“…When the results are examined, it is seen that authors with title of Dr. In contrast with this result, Namdar and Onder (2018) showed that title of thesis supervisors were Assist. Prof. Dr.…”
Section: Discussionmentioning
confidence: 70%
“…Çalışmaların her biri yapıldığı alanla ilgili yeni bilgi birikimleri ve güncel yöntemsel eğilimleri temsil eder (Büyükergün, 2020;Öztürk Kuter ve Öztürk, 2012). Bunlar araştırma yapılan alanla ilgili yayınların eğilimini önemli oranda etkilemekte ve bu eğilim doğrultusunda yapılan araştırmaların yöntemleri de değişebilmektedir (Oğuz Namdar ve Önder, 2019). Bu yüzden yapılan bilimsel çalışmaların incelenmesi yapıldığı alanın bilimsel anlamda ulaşmış olduğu durumun değerlendirilmesine imkân tanıyacaktır (Kaya ve ark., 2016).…”
Section: Introductionunclassified